Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1001/jamainternmed.2017.1068
|View full text |Cite
|
Sign up to set email alerts
|

Association of Statin Use With Risk of Back Disorder Diagnoses

Abstract: Back pain results in tremendous disability and cost; therefore, understanding predisposing or protective factors deserves attention. Statins are widely used, but there is no consensus on whether statins are protective 1 of or deleterious 2-4 to musculoskeletal conditions. A previously published propensity score (PS)-matched study of statin users and nonusers found an association between statin use and increased risk of use-related injury and arthropathies. 2 Scarce data exist on the association of statins with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
(35 reference statements)
0
3
1
Order By: Relevance
“…They described an inversely proportional relationship between the dose of statins prescribed to patients suffering from hypercholesterolemia and the risk of SDJD occurrence 119 . Contrary to the previous reports, a higher risk of developing low back pain was associated with the higher dosage of statins, which tended to cause statin-induced myopathy 120 . With respect to the in vivo and clinical studies, the application of biological treatment strategies for the regeneration of IVDs remains a largely undiscovered field which has great potential for further investigations.…”
Section: Small Molecules and Ivd Regenerationcontrasting
confidence: 91%
“…They described an inversely proportional relationship between the dose of statins prescribed to patients suffering from hypercholesterolemia and the risk of SDJD occurrence 119 . Contrary to the previous reports, a higher risk of developing low back pain was associated with the higher dosage of statins, which tended to cause statin-induced myopathy 120 . With respect to the in vivo and clinical studies, the application of biological treatment strategies for the regeneration of IVDs remains a largely undiscovered field which has great potential for further investigations.…”
Section: Small Molecules and Ivd Regenerationcontrasting
confidence: 91%
“…Previous observational and meta-analysis studies have not been in agreement ( 31 – 33 ) with some studies suggesting no effect ( 34 36 ); however, a nested case-control study ( 29 ) reported that statin use could increase the odds of peptic ulcer by 45% in Korea. We also identified 10 other known statin-related AEs in our study: migraine ( 37 – 39 ), sleep disorder ( 40 42 ), senile cataract ( 21 , 22 ), disorders of vestibular function ( 43 ), GERD ( 44 ), gouts ( 45 ), gonarthrosis ( 46 , 47 ), spondylosis ( 48 ), osteoporosis ( 49 , 50 ), and cystitis ( 51 ). However, all their associations with statin use were weak in both designs, and the biological shreds of evidence for these findings are unidentified.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of the number needed to harm (NNH) in retrospective studies have ranged from 19 to 47 for musculoskeletal disorders [ 7 , 16 , 17 ], and statins markedly increase the risk of myopathy [odds ratio (OR): 2.63, 95% confidence interval (CI): 1.50–4.61] [ 18 ]. A recent analysis considered 60,455 military adults in the TRICARE medical program and propensity matched statin users with nonusers [ 19 ]. The statin users (72% used simvastatin) were observed to have a higher likelihood of back disorder diagnosis (OR: 1.27, 95% CI: 1.19–1.36, NNH = 17 at 4 years).…”
Section: Potential For Adverse Effectsmentioning
confidence: 99%